IMPLEMENTASI KEBIJAKAN PROGRAM RINTISAN MODEL DESA BERDIKARI PROVINSI JAWA TENGAH TAHUN 2015 DI KABUPATEN BLORA - Adi Purwanto (DIA: Jurnal Administrasi Publik, 2018)
Poverty is a social problem that is multidimensional, and therefore requires a comprehensive treatment. Central Java Governor gives a high priority to the problem of handling poverty reduction, according to RPJMD Central Java in 2013-2018. In March 2014 the number of poor people reached 4.836 million (14.46%) with distribution in rural areas as much as 2,891 million (59.78%) and in urban areas as many as 1.945 million people (40.22%). Given the number of poor people in rural areas more than urban areas, and therefore poverty reduction in rural areas needs to be addressed and handled more conceptual, systematic and sustainable. In accordance with the Regulation of the Central Java Governor Number 11 in 2015 on the Financial Aid To the Village Administration To Pioneer Village Model Berdikari In Central Java province Year 20015, then to tackle poverty in Rural Blora been appointed village: Temulus, Sumberejo and Pilang subdistrict of Randublatung as Pilot Model Village Berdikari. Types of Activities chosen to reducing poverty is a goat farm, paving and batik printing. The purpose of this study to determine the extent of the implementation of poverty reduction policies through Pioneer Village Model Berdikari. The method used in this research is qualitative descriptive model. In     analyzing the data obtained in the field by using the theory of Van Meter and Van Horn. Results of this study, that the implementation of the policy of program Pioneer Village Model of Self-reliance can run well, while necessary improvements in terms of regulation, implementation, coordination, communication, synchronization and synergy program between Central Java Provincial Government and District Blora.